2015
DOI: 10.1007/s00170-015-7097-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of process parameters on acceleration amplitude in the drilling of cold work tool steels

Abstract: This study investigated the effects of process parameters on acceleration amplitude in the drilling of AISI D2 and AISI D3 cold work tool steels using HSS twist drills of two different lengths. Workpiece hardness, drill length/tool overhang, cutting speed, feed rate, and number of holes drilled were chosen as the process parameters. In the tests made by using the full factorial (FF) design technique, the values of induced machining vibrations occurring on the workpiece during drilling were specified as the acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Kaplan et al 24 have also found that the tool geometry, cutting speed and feed rate result in vibration of tool.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaplan et al 24 have also found that the tool geometry, cutting speed and feed rate result in vibration of tool.…”
Section: Resultsmentioning
confidence: 99%
“…Kaplan et al 24 have also found that the tool geometry, cutting speed and feed rate result in vibration of tool. Figure 8 shows the effect of interactions of cutting parameters on the acceleration of drill vibration velocity.…”
Section: Anova For Acceleration Of Drill Vibration Velocitymentioning
confidence: 99%
“…On the other hand, the dual-channel MQL system brings air and oil separately within parallel coaxial tubes inside a rotary union; the oil-air mixture is only formed inside the tool assembly and then flowed into the cutting tool channels to reach the tool cutting edges. Although published data for high aspect ratio drilling [2][3][4][5][6][7][8][9], or machining with external MQL [10][11][12][13] have been published, only limited published information for internal MQL was found.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Main effect graphics show the types of effects of dependent variables (output parameters) at different levels of independent variables (input parameters) [54]. In the drilling of Ti-6Al-4V and Al7075 specimens with high-speed steel and tungsten carbide twist drills having same lengths, the main effects of the process parameters on displacement amplitude (Q) shown in figure 8.…”
Section: Main Effects Of Process Parameters On Displacement Amplitudementioning
confidence: 99%